Fundamentals of Artificial Intelligence Research : International Workshop FAIR '91 Smolenice, Czechoslovakia, September 8–13, 1991 Proceedings - Jorrand, Philippe; Kelemen, Jozef; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 1991)
This volume contains 6 invited lectures and 13 submitted contributions to the scientific programme of the international workshop Fundamentals of Artificial Intelligence Research, FAIR '91, held at Smolenice Castle, Czechoslovakia, September 8-12, 1991, under the sponsorship of the European Coordinating Committee for Artificial Intelligence, ECCAI. FAIR'91, the first of an intended series of international workshops, addresses issues which belong to the theoretical foundations of artificial intelligence considered as a discipline focused on concise theoretical description of some aspects of intelligence by toolsand methods adopted from mathematics, logic, and theoretical computer science. The intended goal of the FAIR workshops is to provide a forum for the exchange of ideas and results in a domain where theoretical models play an essential role. It is felt that such theoretical studies, their development and their relations to AI experiments and applications have to be promoted in the AI research community.
User-oriented theorem proving with the ATINF graphic proof editor -- A modal analysis of possibility theory -- Making inconsistency respectable: A logical framework for inconsistency in reasoning, part I — A position paper -- Relational proof systems for some AI logics -- Formal grammars and cognitive architectures -- Efficient simulations of nondeterministic computations and their speed-up by the ring of cooperating machines -- A semantic characterization of disjunctive relations -- Execution of defeasible temporal clauses for building preferred models -- On the phenomenon of flattening “flexible prediction” concept hierarchy -- Possibilistic logic as a logical framework for min-max discrete optimisation problems and prioritized constraints -- An approach to data-driven learning -- Extending abduction from propositional to first-order logic -- Building in equational theories into the connection method -- Logical fiberings and polycontextural systems -- Automated deduction with associative commutative operators -- Towards a lattice of knowledge representation systems -- Inconsistencies handling: nonmonotonic and paraconsistent reasoning -- An approach to structural synthesis of data processing programs -- Negation as failure and intuitionistic three-valued logic -- Symbolic Computation and Artificial Intelligence.
SpringerLink.
Keywords: Computer science; Mathematical logic; Artificial intelligence; Computer Science; Artificial Intelligence (incl. Robotics).; Mathematical Logic and Formal Languages; Mathematical Logic and Foundations